Determinants of Access to Finance on the Development of Small Enterprises in Dar es Salaam, Tanzania - Mgoyi, Mgoi Iddi; Babune, George Julius (Journal of Advanced Research in Humanities and Social Sciences, 2025)
This paper investigated the determinants of access to finance on the performance of small enterprises (SEs) in Dar es Salaam, Tanzania. The paper focused on the variables of access to finance, including financial inclusion, cost of finance, financial literacy, and credit constraints. Understanding these factors was crucial for developing strategies to enhance SE performance and development, given their significant role in regional and national development. A descriptive research design was employed, targeting a population of 318 SE owners. A stratified random sampling method was used to select 150 respondents. Data were collected using a structured questionnaire covering various aspects of finance access. The collected data were analysed using descriptive and inferential statistical methods, including mean, standard deviation, and multiple regression analysis facilitated by SPSS (Statistical Package for the Social Sciences). It was found that financial inclusion (mean = 4.2), financial literacy (mean = 3.8), and credit constraints (mean = 4.3) significantly impact SE access and hence performance. In particular, the financial cost was identified as a critical barrier, with respondents reporting high interest rates (mean = 2.5) that hinder their business decisions. The multiple regression analysis revealed that financial inclusion and financial literacy positively influence SE performance (B = 0.45 and B = 0.25, respectively), while the cost of finance (B = -0.30) and credit constraints (B = -0.40) exert adverse effects. The model explained 72.2% of the variance in SE performance (R² = 0.722). The findings indicated that enhancing financial inclusion and literacy among SE owners is essential for improving their performance. However, high financing costs and credit constraints remain significant challenges that require urgent attention. The study highlights the need for policies to reduce interest rates and improve access to credit for SEs. Financial institutions are recommended to develop tailored financial products that cater to the needs of SEs, emphasising lower interest rates and flexible repayment options.